Diabetes management in Swedish schools: a national survey of attitudes of parents, children, and diabetes teams. Issue 8 (17th March 2014) - Särnblad, S; Berg, L; Detlofsson, I; Jönsson, Å; Forsander, G
<x xml:space="preserve">Abstract</x> Background Parents of children with type 1 diabetes often raise complaints about self‐care support during school time. The aim of this study was to investigate attitudes to diabetes care in school reported by children with type 1 diabetes, their parents, and their diabetes teams. Methods Children who had completed preschool class or at least one grade in the 9‐yr compulsory school system were invited to participate. Data were collected using separate questionnaires for the children and their parents. In addition, the members of the diabetes team answered a separate questionnaire. All pediatric diabetes centers in Sweden were invited to participate in the study. Results All Swedish children and adolescents with diabetes are treated at pediatric diabetes centers. Out of 44 eligible centers, 41 were able to participate. The questionnaires were completed by 317 children and adolescents and 323 parents. The mean age was 11.4 ± 2.7 yr and hemoglobin A1c (HbA1c) was 61.8 ± 12.4 mmol/mol (7.8 ± 1.1%). For 57% of the children, there was no member of staff at the school with principal responsibility to support diabetes self‐care. A written action plan for hypoglycemia existed for 60% of the children. Twenty‐one percent of the parents regularly gave less insulin than they calculated would be needed at breakfast because of fear of hypoglycemia during school time. Conclusions Although Sweden has legislation underlining the specific need for diabetes care in school, this nationwide study demonstrates deficiencies in the support of self‐care management.